2011
DOI: 10.1007/s11136-011-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and extraversion personality traits, health behaviours, and subjective well-being: the Fukuoka Study (Japan)

Abstract: The neuroticism and extraversion scales were associated with health behaviours and BMI differently. The neuroticism scale, but not the extraversion scale, was strongly associated with higher perception of stress, poorer perceived health, and lower satisfaction with life in a Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 34 publications
4
44
0
2
Order By: Relevance
“…The sex difference in the association between Extraversion and BMI, however, was similar to the pattern found in Western samples (Brummett et al, 2006; Sutin & Terracciano, in press). Interestingly, one study of Japanese adults (Kakizaki et al, 2008) found similar sex-specific associations between Neuroticism and Extraversion and body weight and another study (Otonari et al, 2012) also found similar associations, although the authors did not test whether sex moderated these associations (neither study measured Conscientiousness).…”
mentioning
confidence: 99%
“…The sex difference in the association between Extraversion and BMI, however, was similar to the pattern found in Western samples (Brummett et al, 2006; Sutin & Terracciano, in press). Interestingly, one study of Japanese adults (Kakizaki et al, 2008) found similar sex-specific associations between Neuroticism and Extraversion and body weight and another study (Otonari et al, 2012) also found similar associations, although the authors did not test whether sex moderated these associations (neither study measured Conscientiousness).…”
mentioning
confidence: 99%
“…Today, resilience is being studied not only from the perspective of relevance to protection from development of PTSD 11) but also from the genetic and psychobiological perspectives 12,13) , as well as in specific settings such as mass disasters 14) and workplace adversity 15) . Personality traits observed in nonclinical populations are beginning to be considered to be associated with health behaviors or mental well-being 16,17) . Psychiatrists treating personality disorders prefer to categorical approach for its clinical utility 18) ; however, a quantitative review of taxometric research has revealed that the true prevalence of taxonomic findings is smaller than previously thought, especially in the domain of normal personality 19) .…”
mentioning
confidence: 99%
“…Personality plays an important role in perceived physical and emotional health, as its numerous characteristics affect a person's cognitive and emotional judgments of one's health-related quality of life or well-being and, in turn, moderately influence health status or health outcomes. This powerful impact of different personality traits on self-perception has been shown in multiple studies (Diener, 1996;DeNeve & Cooper, 1998;Bal & Sahin, 2011;Otonari et al, 2012). More than three decades ago, Costa and McCrae (1980) indicated that components of neuroticism and extraversion, and not temporary moods or states, can serve to predict individual differences of subjective well--being even over a period of ten years.…”
Section: Introductionmentioning
confidence: 84%